The Man from Boot Hill : Burying the Past - Galloway, Marcus (New York Harper Torch, 2005)
Nick Graves is a Mourner. He arranges funerals and organizes gatherings for wakes as well as hangings, supplementing his meager income by making coffins. He's come to this profession he learned from his father after years making his living with a fast draw and a cool nerve. Nick wants to forget his past by assuming a simple life and a quiet vocation. But the town is full of corrupt men who will make it very difficult for Nick to continue the family trade.
Keywords: Nebraska -- Western stories -- United States--Dakota Territory